2016
DOI: 10.3390/atmos7050069
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Manufacturing Transfer on SO2 Emissions in Jiangsu Province, China

Abstract: Abstract:The impact of manufacturing transfer in Jiangsu province, China, on the spatial-temporal variations of SO 2 emissions is investigated using estimated sector-specific SO 2 emissions, and , respectively. The paper reveals that structure adjustments should be executed in a timely manner in the manufacturing transfer-in process so that the transfer-in regions can benefit from the economic boom without bearing a deteriorated environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, some studies found that industrial structure adjustment has little effect on environmental pollution (Calbick & Gunton, 2014;Cheng et al, 2018;Cole & Elliot, 2003). Some studies even presented the view that industrial structure adjustment does not have an obvious effect on environmental quality (Bruvoll & Medin, 2003;Peng et al, 2016). Other studies found that industrial structure adjustment has a negative effect on environmental quality (Shandra et al, 2008;Guo et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some studies found that industrial structure adjustment has little effect on environmental pollution (Calbick & Gunton, 2014;Cheng et al, 2018;Cole & Elliot, 2003). Some studies even presented the view that industrial structure adjustment does not have an obvious effect on environmental quality (Bruvoll & Medin, 2003;Peng et al, 2016). Other studies found that industrial structure adjustment has a negative effect on environmental quality (Shandra et al, 2008;Guo et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The city data come from the CHINA CITY STATISTICAL YEARBOOK [37] and the official websites of these cities' Statistics Bureaus, while national and provincial data come from the CHINA ENVIRONMENT YEARBOOK [38]. According to lots of previous work, such as the study of Peng et al [39] and Lehoczki and Sleszynski [40], this study chooses industrial SO2 emissions intensity (GDP and per capita GDP used in this paper are based on the benchmark of 2003 at constant price) as an EFT reform evaluation indicator, and the specific equation such as Equation (7). Due to the difference of each city's SO2 emission intensity, the direct use of the difference of emission reduction intensity is not scientific.…”
Section: Data and Sample Selectionmentioning
confidence: 99%
“…In March 2004, Premier Wen Jiabao proposed the "Rise of Central China" [44], followed by a series of plans to stimulate the central region's economy, including Hubei Province. Correspondingly, Hubei Province According to lots of previous work, such as the study of Peng et al [39] and Lehoczki and Sleszynski [40], this study chooses industrial SO 2 emissions intensity (GDP and per capita GDP used in this paper are based on the benchmark of 2003 at constant price) as an EFT reform evaluation indicator, and the specific equation such as Equation (7). Due to the difference of each city's SO 2 emission intensity, the direct use of the difference of emission reduction intensity is not scientific.…”
Section: Data and Sample Selectionmentioning
confidence: 99%
“…Some scholars explored China's SO 2 and NO x discharges from the perspectives of agriculture (Yang et al 2002), transportation, aviation (Qu et al, 2016;Fan et al, 2012), trends, characteristics (Wang et al 2002;Tian et al 2013;Song and Yang 2014), scenarios, forecasting (Vallack et al 2001;Lu et al 2014), and the radiative transfer (Sun et al 2006). Some other scholars have studied the relationship between the two pollutants and respiratory diseases (Ma et al 2016), their co-benefits with carbon reduction (Nam et al 2013), and the assessment of related mitigation policies or strategies (Graus and Worrell 2007;Ying et al 2007;Zhao et al 2013;Peng et al 2016). However, few scientists have studied the drivers of SO 2 and NO x discharges in China from both the periodic Five-Year Plan and the industrial structural perspectives.…”
Section: Introductionmentioning
confidence: 99%